Combined antenna selection and beamforming for secure transmission in distributed antenna systems - Hu Jin; Junsu Kim (International Conference on Information and Communication Technology Convergence (Print), 2013)
In this paper, we propose two combined antenna selection and beamforming schemes: eavesdropper channel nulling (ECN) and distributed phase alignment (DPA), for physical layer security in distributed antenna systems. Two out of all available distributed antennas are selected for secure transmission which is the minimum setting for implementing beamforming. Among all possible two-antenna combinations, the best one that shows the maximum secrecy rate is selected and, therefore, provides a selection gain. ECN cancels the received signal at an eavesdropper when the distributed antennas are subject to a total power constraint. As the distributed antennas may have individual power constraints in practice, we also propose DPA which aligns the phases of the received beams at the eavesdropper to minimize the received signal strength. For ECN with an average total power constraint, we propose an analysis model to track the achievable secrecy rate. Numerical results show that ECN exhibits a closed performance as the optimal beamforming with all distributed antennas.